General average model of T-type three-level converter for active compensation circuit of distribution network - Hao Jin (Elsevier, 2021)
The active compensation device, between the distribution network’s neutral point and the ground, compensates for the single-phase short-circuit current. And the T-type three-level circuit is a possible scheme for compensation devices. This paper proposes the T-type average model based on the above topology, with a controlled voltage/current source, regardless of modulation or control methods. Compared with the two-level converter topology, the three-level converter topology improves the rated voltage stress, with few switching devices’ requirements. The modeling and simulation indicate that the T-type’s average model is identical to its switch model. And the T-type three-level converter can achieve the desired active compensation.